2017
DOI: 10.1097/md.0000000000006549
|View full text |Cite
|
Sign up to set email alerts
|

Treating osteoporotic vertebral compression fractures with intraosseous vacuum phenomena using high-viscosity bone cement via bilateral percutaneous vertebroplasty

Abstract: Osteoporotic vertebral compression fractures with intraosseous vacuum phenomena could cause persistent back pains in patients, even after receiving conservative treatment. The aim of this study was to evaluate the efficacy of using high-viscosity bone cement via bilateral percutaneous vertebroplasty in treating patients who have osteoporotic vertebral compression fractures with intraosseous vacuum phenomena.Twenty osteoporotic vertebral compression fracture patients with intraosseous vacuum phenomena, who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…It has been worried that low-viscosity cement is prone to leak from the vertebra. However, use of high-viscosity cement does not completely prevent the occurrence of leakage [7][8][9][10][11]. In our practice, it was noticed that cement leakage mostly occurs in the late phase of injection, when the cement viscosity is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been worried that low-viscosity cement is prone to leak from the vertebra. However, use of high-viscosity cement does not completely prevent the occurrence of leakage [7][8][9][10][11]. In our practice, it was noticed that cement leakage mostly occurs in the late phase of injection, when the cement viscosity is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…have attempted to challenge this contraindication for vertebroplasty in cases of severe VB collapse with no increase in complication rate 2,6,22,31,33) . Some studies suggested that using high-viscosity bone cement 18) or other equipment like sideopening injection cannulas 26) could prevent cement leakage. Others introduced modified techniques of cement injection in patients with vertebra plana 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that using high-viscosity bone cement 18) or other equipment like sideopening injection cannulas 26) could prevent cement leakage. Others introduced modified techniques of cement injection in patients with vertebra plana 17,18) . We also performed a modified technique of cement injection called eggshell method in patients with severe metastatic compression fractures (MCFs).…”
Section: Introductionmentioning
confidence: 99%
“…With the maturity and wide application of this technology, the extravasation of bone cement is mainly prevented by the choice of bone cement material, the improvement of surgical instruments, the dosage and time of bone cement injection [7] . High viscosity bone cement possesses instant high viscosity, low polymerization temperature and can be injected longtime [8] . It can reduce the polymerization effects of bone cement and thermal of bone cement leakage in the PVP treatment, which may greatly improve the safety of PVP, so as to avoid the occurrence of nerve injury and pulmonary embolism.…”
mentioning
confidence: 99%